2006
DOI: 10.1002/humu.20377
|View full text |Cite
|
Sign up to set email alerts
|

SNPSplicer: systematic analysis of SNP-dependent splicing in genotyped cDNAs

Abstract: Functional annotation of SNPs (as generated by HapMap (http://www.hapmap.org) for instance) is a major challenge. SNPs that lead to single amino acid substitutions, stop codons, or frameshift mutations can be readily interpreted, but these represent only a fraction of known SNPs. Many SNPs are located in sequences of splicing relevance-the canonical splice site consensus sequences, exonic and intronic splice enhancers or silencers (exonic splice enhancer [ESE], intronic splice enhancer [ISE], exonic splicing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 30 publications
0
27
1
Order By: Relevance
“…There have been a few reports of SNPs that do affect splicing (Shinmura et al 2004;Field et al 2005;Skarratt et al 2005;ElSharawy et al 2006;Kawase et al 2007) but no comprehensive analysis of this phenomenon. In our study, we used the 1260 SNPs at 5Јss (dbSNP) (Smigielski et al 2000) that are confirmed by population data and lie outside of positions +1 and +2.…”
Section: Snps At 5јssmentioning
confidence: 99%
“…There have been a few reports of SNPs that do affect splicing (Shinmura et al 2004;Field et al 2005;Skarratt et al 2005;ElSharawy et al 2006;Kawase et al 2007) but no comprehensive analysis of this phenomenon. In our study, we used the 1260 SNPs at 5Јss (dbSNP) (Smigielski et al 2000) that are confirmed by population data and lie outside of positions +1 and +2.…”
Section: Snps At 5јssmentioning
confidence: 99%
“…Previously, Ensembl made its SNP annotation algorithm accessible via the tool “Variant Effect Predictor” [7]. SNP annotation in more specific contexts is furthermore performed by a series of other software tools [812]. However, with the rapid spreading of high-throughput sequencing machines, there is a growing need for high-quality assembly and annotation tools to cope efficiently with the massive amount of sequencing data in respect to annotation and speed data analysis and to extend the analysis to indels.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations that affect splicing appear to be responsible for a large proportion of human genetic diseases (see [5], [6] for reviews) and may even be the largest contributor to human genetic diseases resulting from single point mutations [7]. Researchers investigating the potential functional implications of genetic variants have often tended to ignore splicing effects [5], although, recently, there have been several large-scale studies to identify common genetic variants with an effect on mRNA splicing [4], [8], [9], [10], [11], [12], [13], [14], [15]. These studies parallel efforts to determine the genetic contribution to gene expression variation (for review see [16]).…”
Section: Introductionmentioning
confidence: 99%